Violation of traditional compatibility as a mechanism of appear of the understanding variability (on the example of the Byelorussian internetnews texts) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article it is considered, how violation of traditional compatibility of linguistic units, predefined by the specifics of internet language, complicates understanding of the Byelorussian internet news texts.
Keywords: variability; understanding; violation of compatibility; news sites; internet language; psycholinguistics